ACE Inhibitory and Antioxidative Bioactive Peptides Derived from Hydrolyzed Soy Milk - Hermanto, Sandra; Septiana, Annisa; Putera, Deni K; Hatiningsih, Fitriah; Muawanah, Anna (Molekul, 2019)
Soy milk is a soybean processed product rich in protein as well as sources of bioactive peptides. Bioactive peptides defined as specific protein fragments that have a positive impact on body functions and conditions and may ultimately influence health. This study was conducted to explore the potential of hydrolyzed soy milk as a source of antioxidative and antihypertensive bioactive peptides through enzymatic hydrolysis. The initial treatment of soy milk protein was acidic precipitation with hydrochloric acid. Furthermore, protein precipitate was hydrolyzed using pepsin proteolytic enzyme with an enzyme: substrate ratio (1:5, 1:10 and 1:20). Protein hydrolysis was carried out for 0?48 hours at 37 °C in an acetate buffer pH 4.5. The soy milk protein hydrolysates were subjected to determination of % DH (Degree of Hydrolysis) and protein profile by SDS-PAGE (sodium dodecyl sulphate polyacrylamide gel electrophoresis). The antihypertensive assay was carried out by in vitro inhibition of the ACE enzyme (Angiotensin Converting Enzyme) and antioxidative activity assay using the DPPH method. The results showed that the optimum conditions for hydrolysis of soy milk were obtained at 40 hours with a % DH value of 53.24% in enzyme ratio 1:20 and the highest antihypertensive activity was obtained from 48 hours hydrolysis with % ACE inhibition value of 79.31%. The highest antioxidative activity of bioactive peptide was obtained at hydrolysis 48 hours with IC50 69.1034 µg / ml. After fractionated and LCMS characterized it was obtained 2 bioactive peptides with molecular weights of 8.954 and 2,696 kDa. These bioactive peptides from hydrolyzed of soymilk might be potential as an antihypertensive agent and reduce oxidative stress.